Writing as Resurgent Presencing: An Urban Coyote Curriculum - Hanson, Aubrey Jean (Journal of the Canadian Association for Curriculum Studies, 2023)
In this article, I contemplate the importance of writing to my wellbeing; I reflect on how urban Indigenous presence is enacted and theorized; and I consider an encounter with a coyote during a daily walk. These three narratives are brought together through a textual weaving or métissage. Through this interweaving, and by enacting place-based, relational storying, I undertake a curricular inquiry into presence and presencing. This contemplative inquiry emerges from a particular time and place: from deep in the second winter of the COVID-19 pandemic, from my positionality as an urban Indigenous person, and from my day-to-day existence as a scholar and human being.